Dynamics of photoinduced electron transfer in multiporphyrin nanoassemblies - Kilin, D.; Zenkevich, E.; Borczyskowski, C. von (World Scientific Publishing Co., 2015)
In self-assembled nanoscale porphyrin triads based on Zn-octaethylporphyrin chemical dimer (donor, D) and dipyridyl substituted porphyrin free base (acceptor, A), fluorescence quenching of D (down to 1.7-10 ps) and A (by ~1.3-1.6 times) subunits is strongly dependent on the solvent polarity (toluene-acetone mixtures) and temperature (77-350 K). The obtained experimental findings are analyzed using the reduced density matrix formalism in the frame of Haken-Strobl-Reineker approach taking into account the energy transfer, charge separation, and the dephasing of coherence between the excited electronic states of the triad.